Non-linear Behavior of Low Strength RC Beams Strengthened with CFRP Sheets - Ahmed Mohammed Youssef Mohammed; Abdul Rahman Mamoun Ali; Hany Ahmed Abdalla (Civil Engineering Journal, 2021)
There are many modern technologies for strengthening concrete. One of them is Carbon Fiber Reinforcement Polymer (CFRP) sheets. There are many cases that require concrete strengthening, including the weakness of concrete from the design strength due to the exposure of the concrete elements to fires or less control of concrete quality. This research provides a theoretical study to analyze the behavior of low strength RC beams strengthened with CFRP sheets using ANSYS software. The research contained (75) RC beam model specimens. Six of them for verifying results with experimental tests. Forty five specimens were used for studying flexural behavior and twenty four beam models used for studying shear behavior. The study conducted with variable parameters includes CFRP thickness, concrete strength, the yield stress of steel, and the application of CFRP plies. The theoretical results were very similar to experimental test results. The results proved that strengthening RC beams is increasing load capacity and it is very effective in case of low yield stress of steel. Doi: 10.28991/cej-2021-03091670 Full Text: PDF